Pentecostalism and the Construction of Socio-Political Identities - Nicolás Panotto (Desafíos, 2014)
This article introduces the notion of identity from various current approaches —such as poststructuralist and postcolonial theories within the area of philosophy as well as anthropology— and how identity, taking into account the plurality of contemporary social subjects such as religious communities, enables the expansion of the study of political dynamics. As a specific case study, a neopentecostal community in Buenos Aires, Centro Cristiano Nueva Vida (cnvc) is selected. The article analyzes how this church builds its socio-political identity in light of its religious specificity: theological discourses, symbolic processes, rituals, and institutional methods.